Co-creation of health-enabling initiatives in food retail: academic perspectives - Carmen Vargas; Julie Brimblecombe; Steven Allender; Jillian Whelan (BMC, 2023)
Abstract Introduction Co-creation of healthy food retail comprises the systematic collaboration between retailers, academics and other stakeholders to improve the healthiness of food retail environments. Research into the co-creation of healthy food retail is in its early stages. Knowledge of the roles and motivations of stakeholders in intervention design, implementation and evaluation can inform successful co-creation initiatives. This study presents academic experiences of stakeholder roles and motivations in the co-creation of healthy food retail environments. Methods Purposive sampling of academics with research experience in the co-creation of healthy food retail initiatives. Semi-structured interviews conducted between October and December 2021 gathered participants' experiences of multi-stakeholder collaborative research. Thematic analysis identified enablers, barriers, motivations, lessons and considerations for future co-creation of healthy food retail. Results Nine interviewees provided diverse views and applications of co-creation research in food retail environments. Ten themes were grouped into three overarching areas: (i) identification of stakeholders required for changes to healthier food retail; (ii) motivations and interactions, which included the intrinsic desire to build healthier communities along with recognition of their work; and (iii) barriers and enablers included adequate resourcing, effective and trusting working relationships and open communications. Conclusion This study provides insights that could help future co-creation in healthy food retail environments. Trusting and respectful relationships and reciprocal acknowledgement between stakeholders are key practices in the co-creation process. These constructs should be considered in developing and testing a model that helps to systematically co-create healthy food retail initiatives that ensure all parties meet their needs while also delivering research outcomes.